2012
DOI: 10.1371/journal.pone.0051119
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 and Hey-1 as Prognostic Biomarkers in Pancreatic Adenocarcinoma

Abstract: In order to achieve a better outcome for pancreatic cancer patients, reliable biomarkers are required which allow for improved diagnosis. These may emanate from a more detailed molecular understanding of the aggressive nature of this disease. Having previously reported that Notch3 activation appeared to be associated with more aggressive disease, we have now examined components of this pathway (Notch1, Notch3, Notch4, HES-1, HEY-1) in more detail in resectable (n = 42) and non-resectable (n = 50) tumours compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…However, the present data demonstrated that Notch 3 is (8,9,13). The mechanism of this phenomenon and how Notch 3 exerts its function in NSCLC remain unclear and require further research.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the present data demonstrated that Notch 3 is (8,9,13). The mechanism of this phenomenon and how Notch 3 exerts its function in NSCLC remain unclear and require further research.…”
Section: Discussionmentioning
confidence: 58%
“…The activation of Notch 1 signaling appears to sustain the motility, migration and invasion of tumor cells in esophagus squamous cell carcinomas, lingual squamous cell carcinoma, endometrial carcinoma and breast cancer (11)(12)(13)(14)(15). Almost all cases of T cell acute lymphoblastic leukemia (T-ALL), and colorectal, pancreatic and ovarian cancer have been reported to exhibit aberrant Notch 3 expression (6,8,16,17). Our previous study also reported that Notch 3 overexpression was associated with a poor prognosis in NSCLC patients (18).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Increased Notch3 protein levels have been identified as a prognostic marker for patients with PDAC (Mann et al ., 2012), and lead to increased tumor invasion, metastasis, and shortened patient survival (Zhou et al ., 2016). Because of this, Notch3 has become a target for novel cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous findings revealed that the activation of Notch4 promoted GC cell growth in vitro and in vivo, while the inactivation of Notch4 by siRNA had the opposite effects (6). In the present study, it was demonstrated Notch expression in PC was correlated with serosal invasion, lymph node metastasis, histopathological grading, tumor-node-metastasis stage and recurrence (21)(22)(23)(24). Enhanced Notch4 expression in salivary adenoid cystic carcinoma may stand as a novel mechanism for promoting metastasis (25).…”
Section: Discussionmentioning
confidence: 53%